Protected plant species of forest, lakes and peatbogs in the Western Part of the Drawskie Lakeland - Umiastowska, Marta; Ciaciura, Marian (Biodiversity: Research and Conservation, 2010)
A floristic study of forest communities, lakes, and peatbogs of the western part of the Drawskie Lakeland was carried out in 2006-2008. The study revealed the presence of numerous valuable plant species. More than 400 floristic lists were compiled. Plant surveys were conducted with the aid of the ATPOL square grid system. To increase the accuracy of the surveys, the basic ATPOL squares (10x10 km) were additionally subdivided into smaller ones of 1x1 km. The area of study was found to support 416 plant species, including protected ones: 17 species strictly protected (e.g., Blechnum spicant, Dactylorhiza incarnata, Drosera rotundifolia, Lycopodium annotinum, Utricularia intermedia) and 12 under partial protection (e.g., Frangula alnus, Menyanthes trifoliata, Ononis spinosa, Ribes nigrum, Viburnum opulus). The list of protected plants contains one species (Lobelia dortmanna) included in the Polish Red Book of Plants.